Percorrendo as imagens do livro didático de língua inglesa com vistas para além dos territórios nativos da anglofonia: uma análise de suas páginas de abertura - Costa, Walison Paulino de Araújo (2016)
This thesis frames an analytical discussion on the linguistic education, based on the imagetic standards found in the English textbooks, grounded on concepts such as teaching of English in a pluricentric approach, interculturality, multiculturalism, language/culture, going further into matters that deal with beliefs and teacher education, whose repercussion reaches its summit level in the last chapter. Thus, we aim at analyzing the images of the textbooks pertaining to PNLD in 2012, having as the starting point the concept of English as an international/pluricentric language/lingua franca, which makes possible that learners can look at themselves inserted like protagonists of a language/culture; although it is still regarded as a ‘foreign’ language, those learners can make use of it in contexts where they may also deal with images. In methodological terms, we selected the 7 (seven) textbook sets, including three-level textbooks each set, since it is a unique moment for the history of language teaching in Brazil: it is the first time that English textbooks for secondary school were included by Programa Nacional do Livro Didático into the area Language, Codes and its Technologies (BRAZIL, 2011, p. 07). To continue, we were based on the criteria we created for the definite choice of the 17 (seventeen) pages that constitute our corpus, 16 (sixteen) images in the unit entries and 01 (one) image in the entry of the book as a whole. We analyzed one by one. Qualitatively and quantitatively the results showed that the countries that make imagetic reference to the internal circle by Kachru (1985) are predominant, owing to the spaces they take up and how they do it. Based on the categories that come from the Grammar of Visual Design, by Kress and van Leeuwen (2006), more precisely, the compositional metafunction and its interrelated systems, we conclude: readers/observers, in this case, learners, are not involved by a pluricentric concept of the English language, since the supremacy of native English speakers and their linguistic-cultural standards dominate in the pages of the textbooks mentioned, but the imagetic references to England and mainly to the United States of America are deemed prime.